Coordinated Ground‐Based and Space‐Based Observations of Equatorial Plasma Bubbles. Issue 1 (13th January 2020) - Aa, Ercha; Zou, Shasha; Eastes, Richard; Karan, Deepak K.; Zhang, Shun‐Rong; Erickson, Philip J.; Coster, Anthea J.
Abstract: This paper presents coordinated and fortuitous ground‐based and spaceborne observations of equatorial plasma bubbles (EPBs) over the South American area on 24 October 2018, combining the following measurements: Global‐scale Observations of Limb and Disk far ultraviolet emission images, Global Navigation Satellite System total electron content data, Swarm in situ plasma density observations, ionosonde virtual height and drift data, and cloud brightness temperature data. The new observations from the Global‐scale Observations of Limb and Disk/ultraviolet imaging spectrograph taken at geostationary orbit provide a unique opportunity to image the evolution of plasma bubbles near the F peak height over a large geographic area from a fixed longitude location. The combined multi‐instrument measurements provide a more integrated and comprehensive way to study the morphological structure, development, and seeding mechanism of EPBs. The main results of this study are as follows: (1) The bubbles developed a westward tilted structure with 10–15° inclination relative to the local geomagnetic field lines, with eastward drift velocity of 80–120 m/s near the magnetic equator that gradually decreased with increasing altitude/latitude. (2) Wave‐like oscillations in the bottomside F layer and detrended total electron content were observed, which are probably due to upward propagating atmospheric gravity waves. The wavelength based on the medium‐scale traveling ionospheric disturbance signature was consistent with the interbubble distance of ∼ 500–800 km. (3) The atmospheric gravity waves that originated from tropospheric convective zone are likely to play an important role in seeding the development of this equatorial EPBs event. Plain Language Summary: This study presents multi‐instrument observations of equatorial plasma density depletions occurred on 24 October 2018 by using Global‐scale Observations of Limb and Disk far ultraviolet images, Global Navigation Satellite System total electron content data, electron density measurements from Swarm satellite, ionosonde measurements, and cloud temperature data. This multi‐instrument study generated an integrated and detailed image revealing both large‐scale and mesoscale structures of the equatorial plasma depletion. Our results also suggest that atmospheric gravity waves originating from tropospheric convection activity could play a significant seeding role in the development of equatorial plasma bubbles. Key Points: Combined GOLD/UV spectrograph images and ground‐based TEC data revealed EPB features and development over a large geographic area Bottomside F layer oscillations and traveling ionospheric disturbance were observed by ionosonde and detrended TEC results Atmospheric gravity waves likely play an important role in seeding the R‐T instability and the development of this EPB event